Maternal Knowledge of Stunting in Rural Indonesia - Hall, Cougar; Bennett, Cudjoe; Crookston, Benjamin; Dearden, Kirk; Hasan, Muhamad; Linehan, Mary; Syafiq, Ahmad; West, Scott; West, Joshua (International Journal of Child Health and Nutrition, 2018)
Child undernutrition and stunting remain serious public health problems in Indonesia. According to the Health Belief Model, increasing mothers’ knowledge of stunting is fundamental to establishing accurate threat perceptions predictive of behavior change. The purpose of this study was to increase understanding of factors related to maternal knowledge of stunting in Indonesia by addressing three questions: 1) How familiar with stunting are Indonesian mothers? 2) What antecedent factors do Indonesian mothers associate with stunting? and 3) What health effects do Indonesian mothers associate with stunting? A total of 3,150 mothers participated in structured face-to-face interviews. Study measures targeted four main variables. Mothers were asked: 1) Have you heard of stunting?; 2) Have you heard of shortness?; 3) What causes stunting/shortness?; and 4) What are the effects of stunting? Only 66 (2.1%) mothers reported having heard of, read about, or knew something about stunting. Approximately two-thirds of participants attributed stunting to hereditary factors. Interrupted growth (33.7%), idiocy (13.8%), and easy to get sick (11.8%) were identified as health effects of stunting. Results highlight the need for health promotion and education efforts focused on increasing basic knowledge of stunting, its causes, and its health effects among Indonesian mothers